Edukasi Postur Tubuh yang Baik dalam Kesehatanu Pencegahan Low Back Pain Pada Warga Kelurahan Semanggi - Arif Pristianto; Muhammad Sena Nurrahman Pasya; Ariq Windra Nugraha; Atikah Nurulinsani; Ardhita Hilwa Zakia; Nabilah Tri Sulistiowati (Indonesian Journal of Community Services in Engineering & Education (IJOCSEE), 2023)
Back pain is widespread in various adult populations. Several studies have shown that 23% of adults worldwide suffer chronic low back pain. The activity program implemented is education on good body posture in health to prevent low back pain. The target audience for this activity is residents. The program method is carried out by counseling in the form of lectures. This activity has resulted in the delivery of education regarding good posture for health and prevention of the risk of low back pain in the community so that the implications received by the community can understand good posture for health and prevention of the risk of low back pain, as well the community has been able to do several exercises as a form of prevention and reduction of pain in the lower back.